CAPM model applied to the Portuguese stock market - Teixeira, N.; Silva, M.; Vinhas da Silva, R.; Pereira, L.; Vinhas da Silva, S. (International Journal of Electronic Finance, 2023)
The stock market volatility is well correlated with the VUCA (volatility, uncertainty, complexity, and ambiguity) environment, so it's important to understand the best techniques that capture this relationship. The main objective of this work is to analyse the capital asset pricing model (CAPM) to understand the relationship between risk and return. The other objective is to try to understand if the CAPM model is reflected in the Portuguese stock exchange. If there is a direct correlation between risk and expected return, then we are looking at an efficient market. Through the method of observation and bibliographic and documentary research, a practical assessment is made of the relationship between the CAPM model and the Portuguese stock exchange. Analytically, an analysis of 40 companies of the Portuguese stock index (PSI 20) is carried out, where the behaviour of the beta and the rate of return is demonstrated.